Near-Field Electromagnetic Scatterings and Imaging of a Ship Based on High-Frequency Techniques - Conghui Qi; Wei Yang; Xiaozhang Zhu (International Journal of Antennas and Propagation)
In radar detection, it is important to investigate the near-field scattering characteristics since the far-field condition is not easily satisfied for the distance between the radar and the electrically large ship on the sea surface. A high-frequency techniques of the physical optics (PO) and shooting and bouncing rays (SBR) with local expansions based on the facets of the target are proposed to take the electromagnetic scatterings in the near zone. Therefore, it is a more straightforward method to modify the computation from traditional far-field problem to near-field problem with the singularity-free characteristic. Simulation results show that it has high accuracy but requires very little increase in computational costs in the near-field problem. Moreover, the 1-D high-resolution range profile (HRRP) demonstrates that the near-field scattering mechanism is much different from the cases in the traditional far-field problem.